Influence of carbohydrate, intense exercise, and rest intervals on hormonal and oxidative changes - McAnulty, S. R.; McAnulty, L. S.; Morrow, J. D.; Nieman, D. C.; Owens, J. T.; Carper , C. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
This study compared effects of carbohydrate (CHO) and rest on oxidative stress during exercise. Cyclists (N = 12) completed 4 randomized trials at 64% Wattsmax under 2 conditions (continuous cycling for 2 h [C] and cycling with 3-min rest every 10 min for 2.6 h [R]). Subjects cycled under each condition while receiving 6% CHO and placebo (PLA). CHO and PLA were given preexercise (12 mL/kg) and during exercise (4 mL·kg-1·15 min-1). Blood was collected preexercise, postexercise, and 1 h postexercise and assayed for F2-isoprostanes, hydroperoxides (LH), nitrite, antioxidant capacity, glucose, insulin, cortisol, and epinephrine. F2-isoprostanes and LH were lower in CHO. Glucose, cortisol, and epinephrine exhibited significant effects, with postexercise levels of glucose higher and cortisol and epinephrine lower in CHO during the R condition. This pattern was identical in the C condition (21). Oxidative stress during cycling was unaffected by use of short rest intervals but was diminished by CHO.